Body Image Perception of Obese Individuals Monitored at the Endocrinology Clinic - Bonamich, Beatriz Dal Santo Francisco; Santos, Rafael Bonamichi dos; Amigo, Veruska Lastoria (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Evaluate body self-perception of obese patients monitored in an endocrinology clinic.Method: Cross-sectional study, with data obtained via interviews from fifty obese patients receivingtreatment at the Endocrinology Clinic. We used a questionnaire asking about personal characteristics,comorbidities, medication, daily habits, and the calculation of Body Mass Index (BMI) for theclassification of obesity according to sample variables defined by Cole et al. Body image was determinedusing the silhouette scale. Results: predominance of females with an association of obesity to othercomorbidities such as diabetes mellitus, dyslipidemia, and arterial hypertension. In 44% of patients, thepredominant behavioral profile was anxiety. The cause attributed to weight gain in 22% of cases waspregnancy, and emotional problems in 44.4%. Currently, 44% of patients assessed in this study are usingadjuvant medication for weight loss, with sibutramine prescribed in 24% of cases. All these patients received relevant nutritional guidance. 40% of patients undertake physical activity. The main motivationfor weight loss was health (48%). We can see that there is a significant variability in the distortion ofbody image, mainly with women, whereby 51.1% believe that their BMI is 2.5 points below the reallevel. In terms of intention, 40% wished to lose 5 points on the BMI, with the majority still classifyingthemselves as overweight even with this level. Conclusion: This study showed a distortion of bodyimage, especially amongst women, demonstrating that they idealize an image less obese than what theyreally show themselves to be.